Clinical and genetic features of cervical dystonia in a large multicenter cohort. (June 2016) - LeDoux, Mark S.; Vemula, Satya R.; Xiao, Jianfeng; Thompson, Misty M.; Perlmutter, Joel S.; Wright, Laura J.; Jinnah, H.A.; Rosen, Ami R.; Hedera, Peter; Comella, Cynthia L.; Weissbach, Anne; Junker, Johanna; et al.
Abstract : Objective: To characterize the clinical and genetic features of cervical dystonia (CD). Methods: Participants enrolled in the Dystonia Coalition biorepository (NCT01373424) with initial manifestation as CD were included in this study (n = 1, 000). Data intake included demographics, family history, and the Global Dystonia Rating Scale. Participants were screened for sequence variants (SVs) in GNAL, THAP1, and Exon 5 of TOR1A . Results: The majority of participants were Caucasian (95%) and female (75%). The mean age at onset and disease duration were 45.5 ± 13.6 and 14.6 ± 11.8 years, respectively. At the time of assessment, 68.5% had involvement limited to the neck, shoulder(s), and proximal arm(s), whereas 47.4% had dystonia limited to the neck. The remaining 31.5% of the individuals exhibited more extensive anatomical spread. A head tremor was noted in 62% of the patients. Head tremor and laryngeal dystonia were more common in females. Psychiatric comorbidities, mainly depression and anxiety, were reported by 32% of the participants and were more common in females. Family histories of dystonia, parkinsonian disorder, and tremor were present in 14%, 11%, and 29% of the patients, respectively. Pathogenic or likely pathogenic SVs in THAP1, TOR1A, and GNAL were identified in 8 participants (0.8%). Two individuals harbored novel missense SVs in Exon 5 of TOR1A . Synonymous and noncoding SVs in THAP1 and GNAL were identified in 4% of the cohort. Conclusions: Head tremor, laryngeal dystonia, and psychiatric comorbidities are more common in female participants with CD. Coding and noncoding variants in GNAL, THAP1, and TOR1A make small contributions to the pathogenesis of CD.